Toxic epidermal necrolysis caused by viral hepatitis A: a case report and literature review - Ye, Yun; Zhang, Qian; Tan, You-Wen (Frontiers in Medicine, 2024)
Toxic epidermal necrolysis (TEN) is a rare but serious immune-mediated life-threatening skin and mucous membrane reaction that is mainly caused by drugs, infections, vaccines, and malignant tumors. A 74-year-old woman presented with a moderate fever of unknown cause, which was relieved after 2 days, but with weakness and decreased appetite. Red maculopapules appeared successively on the neck, trunk, and limbs, expanding gradually, forming herpes and fusion, containing a yellow turbidous liquid and rupturing to reveal a bright red erosive surface spreading around the eyes and mouth. The affected body surface area was >90%. The severity of illness score for toxic epidermal necrolysis was 2 points. The drug eruption area and severity index score was 77. She was diagnosed with TEN caused by hepatitis A virus and treated with 160 mg/day methylprednisolone, 300 mg/day cyclosporine, and 20 g/day gammaglobulin. Her skin showed improvements after 3 days of treatment and returned to nearly normal after 1 month, and liver function was completely normal after 2 months.